Effect of Kratom (Mitragyna speciosa) Hydrogel on Liver Function in Diabetic Burn Injury - Pramesti, Rosandhy Alifyah Pramesti; Jazuli, Muhammad Aqil Siroj; Ismail, Zainul Hadi Wildan; Rihhadatulays, Khuzaimah Nur Juhanifah; Hanafi, Eka Satria Akbar Ferdinan; Jinan, Puspita Rahmatul; Salim, Hotimah Masdan; Bermawi, Bastiana (Jurnal Medis Islam Internasional, 2025)
Introduction: Burns are serious injuries that not only damage the skin but can also affect internal organs such as the liver. Severe inflammation following burn injury increases hepatocyte vulnerability, especially in diabetic conditions. Objective: This study aimed to evaluate the effect of topical kratom (Mitragyna speciosa) hydrogel on liver histopathology in streptozotocin-induced diabetic mice with burn injuries. Methods: An in vivo experimental study with a post-test-only control group design was conducted using 15 male musmusculus. Diabetes mellitus was induced prior to burn injury, and hyperglycemia was confirmed before further procedures. The diabetic mice were then randomly assigned into three groups: diabetic burn injury without hydrogel treatment (K), diabetic burn injury treated with 5% kratom hydrogel (T1), and diabetic burn injury treated with 15% kratom hydrogel (T2). The respective treatments were applied for four weeks. Following the intervention period, liver tissues were collected for histopathological analysis. Hepatocyte damage was quantitatively assessed and analyzed using one-way ANOVA followed by Dunnett’s post hoc test. Results: The diabetic burn injury control group exhibited the greatest extent of hepatocyte damage (66.5 ± 5.0%). Application of 5% kratom hydrogel (49.5 ± 4.0%) and 15% kratom hydrogel (52.5 ± 4.0%) resulted in a statistically significant reduction in hepatocyte injury compared with the diabetic control group (p = 0.0043 and p = 0.0131, respectively). Conclusions: Topical administration of kratom hydrogel significantly attenuated hepatocyte damage in diabetic mice subjected to burn injuries, suggesting a hepatoprotective effect and potential benefits for preserving liver function under diabetic burn conditions.